The vertical Na–O relation in the bulge globular cluster NGC 6553. Issue 3 (23rd January 2020) - Muñoz, C; Villanova, S; Geisler, D; Cortés, C C; Moni Bidin, C; Cohen, R E; Saviane, I; Dias, B; Tang, B; Mauro, F
ABSTRACT: In this article, we present a detailed chemical analysis of seven red giant members of NGC 6553 using high-resolution spectroscopy from VLT FLAMES. We obtained the stellar parameters ( T eff, Log( g ), v t, [Fe/H]) of these stars from the spectra, and we measured the chemical abundance for 20 elements, including light elements, iron-peak elements, α-elements, and neutron-capture elements. The metallicities in our sample stars are consistent with a homogeneous distribution. We found a mean of [Fe/H] = −0.14 ± 0.07 dex, in agreement with other studies. Using the α-elements Mg, Si, Ca, and Ti, we obtain the mean of [α/Fe] = 0.11 ± 0.05. We found a vertical relation between Na and O, characterized by a significant spread in Na and an almost non-existent spread in O. In fact, Na and Al are the only two light elements with a large intrinsic spread, which demonstrates the presence of multiple populations (MPs). An intrinsic spread in Mg is not detected in this study. The α, iron-peak, and neutron-capture elements show good agreement with the trend of the bulge field stars, indicating similar origin and evolution, in concordance with our previous studies for two other bulge globular clusters (NGC 6440 and NGC 6528).